Variation of Pronunciation Norm and Meaning in Light of Semantic-Cognitive Analysis: german Idiom das A und O - K. V. Manerova (Научный диалог, 2022)
A unique example for the German language of the divergent development of the pronunciation norm and frame semantics in the phraseological unit das A und O and variants das Alpha und Omega / das Alpha und O / A und O. The interpretation of the pronunciation norm from the theoretical works of L. A. Verbitskaya is used. Observations on the development of semantic frames are presented on the basis of semantic-cognitive analysis and sociophonetic analysis of the pronunciation norm of a grapheme phraseological unit. The loss of religious connotation during the transition of the phrase into profane discourse in the course of discursive secularization is noted. The influence of the written norm on the oral norm is established as the reason for the emergence of the variance of the phraseological unit in diachrony. The emergence of variance of a grapheme formula in the direction of reduction of its components is studied. Mechanisms for modeling the meaning of idiom variants by means of four cognitive operations are disclosed. The study of formula norm dynamics is confirmed by examples of codification in nine German dictionaries. The relevance of the study is due to the application of corpus analysis to 14743 contextual uses of the formula das A und O in texts from the digital corpus of the German language DWDS. It is concluded that the pronunciation norm in its dynamics regulates the functioning of this phraseological unit in literary German.